2016
DOI: 10.1002/jcla.22089
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis index to detect degree of hydroxocobalamin interference with common laboratory tests

Abstract: OHCo interferes with many laboratory assays in an unpredictable way making some results invalid and confounding clinical decision making. We can detect and evaluate the degree of interference with the HI. We can still estimate real creatinine and lactate levels using the regression equation obtained in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The red discoloration of body fluids after OHCob administration makes laboratory evaluation by spectrophotometric techniques erroneous. 16 Of greatest concern is the accuracy of COHb concentrations. 17 In a study using rabbit models by Lee et al, 17 OHCob administration was shown to falsely increase COHb concentrations.…”
Section: Effect Of Hydroxocobalamin On Laboratory Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The red discoloration of body fluids after OHCob administration makes laboratory evaluation by spectrophotometric techniques erroneous. 16 Of greatest concern is the accuracy of COHb concentrations. 17 In a study using rabbit models by Lee et al, 17 OHCob administration was shown to falsely increase COHb concentrations.…”
Section: Effect Of Hydroxocobalamin On Laboratory Evaluationmentioning
confidence: 99%
“…Of particular clinical importance, a falsely increased lactate level was seen after true lactate levels were found to be below 4.8 mmol/L (but not greater) using spectrophotometric or electrochemical detection. 21 This increase in the false-positive assessment of the degree of toxicity could lead unnecessary escalation of care.…”
Section: Examining the Effects Of Ohcob Onmentioning
confidence: 99%